2008
DOI: 10.1095/biolreprod.107.065987
|View full text |Cite
|
Sign up to set email alerts
|

A Mutation in the Inner Mitochondrial Membrane Peptidase 2-Like Gene (Immp2l) Affects Mitochondrial Function and Impairs Fertility in Mice1

Abstract: The mitochondrion is involved in energy generation, apoptosis regulation, and calcium homeostasis. Mutations in genes involved in mitochondrial processes often result in a severe phenotype or embryonic lethality, making the study of mitochondrial involvement in aging, neurodegeneration, or reproduction challenging. Using a transgenic insertional mutagenesis strategy, we generated a mouse mutant, Immp2lTg(Tyr)979Ove, with a mutation in the inner mitochondrial membrane peptidase 2-like (Immp2l) gene. The mutatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

18
168
1
6

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 105 publications
(193 citation statements)
references
References 47 publications
18
168
1
6
Order By: Relevance
“…Our observation of increased protein nitration in old mutant mice is consistent with our previous observation of excessive superoxide generation from mitochondria of mutant mice (Lu et al ., 2008). Physiological levels of nitric oxide are necessary for the survival of differentiated cerebellar granule cells (Ciani et al ., 2002).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Our observation of increased protein nitration in old mutant mice is consistent with our previous observation of excessive superoxide generation from mitochondria of mutant mice (Lu et al ., 2008). Physiological levels of nitric oxide are necessary for the survival of differentiated cerebellar granule cells (Ciani et al ., 2002).…”
Section: Resultsmentioning
confidence: 99%
“…nNOS is highly expressed in cerebellar granule neurons (Bredt et al ., 1990; Bredt & Snyder, 1992). We previously reported that −/− mice show erectile dysfunction and decreased hypothalamic cGMP level (Lu et al ., 2008; Han et al ., 2013), both could result from negation of nitric oxide by mitochondrial superoxide. Quantitative RT–PCR revealed that nNOS and iNOS expression were increased in cerebella of young mutant mice, whereas eNOS expression was not significantly different between +/+ and −/− mice regardless of age (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations